Baseline triglycerides and non-HDL-C and apoB goal attainment in the ORION-10 and ORION-11 trials. (25th November 2020) - Ray, K.K; Kallend, D; Raal, F.J; Stoekenbroek, R; Koenig, W; Leiter, L.A; Landmesser, U; Schwartz, G.G; Wijngaard, P.L.J; Kastelein, J.J.P; Wright, R.S
Abstract: Introduction: Elevated triglyceride (TG) levels contribute to the total burden of circulating atherogenic lipoprotein levels and are associated with increased cardiovascular (CV) risk. LDL-C underestimates risk in patients with elevated TG. Therefore, 2019 ESC/EAS guidelines recommend apoB or non-HDL-C as secondary lipid goals for patients with TG >150mg/dL. Purpose: To assess the impact of inclisiran on apoB and non-HDL-C goal attainment across a range of TG levels among patients with atherosclerotic CV disease (ASCVD). Methods: The ORION-10 and ORION-11 trials included 3178 patients with ASCVD and LDL-C >70mg/dl despite maximally tolerated statins randomized to inclisiran or placebo (1:1). Pre-specified secondary endpoints were placebo-corrected changes in lipids at Day 510. For this analysis patients were stratified by TG quartiles at baseline within each trial. The proportion of individuals attaining apoB <55 mg/dL or non-HDL-C <70mg/dl within each trial were assessed across TG strata and the likelihood of goal attainment within TG strata assessed using logistic regression. Results: In ORION-10, TG quartiles were ≤94, 94 to ≤128, 128 to ≤181 and >181mg/dl respectively and in ORION-11 corresponding values were ≤101, 101 to ≤135, 135 to ≤183 and >183mg/dl. As compared to placebo a significantly greater proportion of patients randomised to inclisiran attained apoB goals within each TG strata (Table). Similar results were observed for non-HDL-C. Conclusion: Among patients with ASCVD on maximally tolerated statin and high TG levels, attainment of apoB and non-HDL-C secondary lipid targets was more likely with inclisiran than placebo. Inclisiran may be a useful therapeutic option for patients with atherogenic dyslipidaemia. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): The Medicines Company